PRICE PERCEPTION, VARIETY SEEKING, DAN ELECTRONIC WORD OF MOUTH TERHADAP STORE SWITCHING DALAM BELANJA ONLINE PADA TOKOPEDIA DI KOTA DENPASAR - Desak Made Febri Purnama Sari; Marsyah Fiolita (JUIMA : JURNAL ILMU MANAJEMEN, 2021)
This study aims to determine the effect of price perception, variety seeking, electronic word of mouth on store switching in online shopping on Tokopedia. The population of this research is consumers who have Tokopedia application in Denpasar City, with a sample of 80 respondents. Sampling using a purposive sampling technique. Collecting data using an online questionnaire with a Likert scale measurement tool. The type of data used in this study is quantitative data. The data analysis method used in this study uses validity test, reliability test, classic assumption test, and multiple linear regression analysis test using the SPSS version 20.0 application. The results of this study stated that the variable price perception, variety seeking, electronic word of mouth had a positive and partially significant effect simultaneously on store switching in online shopping at Tokopedia in Denpasar City, with the variable X1 Price perception having the strongest influence with a beta coefficient of 0.352 because in shopping online or offline the first thing that consumers see is the price of a product with different perceptions for each consumer to see the usefulness, value, and quality of the product through the price consumers want.